Soul wisdom : practical treasures to transform your life - Sha, Zhi Gang (New York : Atria Books, 2008)
In Soul Wisdom, internationally acclaimed Soul Master, healer, and bestselling author Dr. Zhi Gang Sha takes healing and personal transformation to the ultimate level, the soul level. Dr. Sha's teachings empower you to melt all of your life blockages with practical soul treasures: Soul Language, Soul Song, Soul Movement, Soul Tapping, and Soul Dance. This is the first time in history that the Divine has released these soul secrets to transform the consciousness of humanity and create love, peace, and harmony for humanity, Mother Earth, and the Universe. "The Soul Song for Healing and Rejuvenation" included in this book is an MP3 file that only some CD players can play. If your CD player cannot play MP3 files, you can download a music file at http://www.drsha.com and burn it to a CD that will work on virtually all CD players.
" A previous verison of this work was published by Heaven's Library Publication Corp. in 2007"--T.p. verso.
Keywords: Spiritual life; Spiritual healing